Modernisasi Pendidikan Agama Islam Di Era Revolusi Industri 4.0 - Bali, Muhammad Mushfi El Iq; Hajriyah, Hilya Banati (MOMENTUM : Jurnal Sosial dan Keagamaan, 2020)
Industry progress has required people to have the ability to face all the challenges that exist today, the industrial revolution 4.0, brought an impact on human life. Educational institutions are expected to be resilient in the face of obstacles and challenges as well as changes that occur within communities both local, regional, national, and global communities. In anticipation of the negative impact of the advancements of science and the pace of modernization, individuals must immediately recognize and fortify themselves with the various abilities of religious science in each individual. The research method uses the library research method of the library research to explore a data source consisting of literature literature linked to the modernization of education in the era of industrial revolution 4.0, they should be able to create a successful and successful generation; hence, moral education becomes the filter for foreign cultural values, which are not compatible with Islamic or Indonesian culture.